An Investigation Into The Efficacy Of Radiotherapy Protocols For The Treatment Of Lung Carcinoma And The Optimization Of Dosimetry Calculations - alotibi, Jawaher nasser; Alanazi, Mashael dhafi dhuwayhi; Alanazi, Nasser dhafi dhuwayhi; Almutairi, Saad sunitan; alotaibi, Salma saud wajib; Alotaibi, Manal fadha mushi; Alotaibi, Sarah falah; Hamdi, Afaf Ali Abdullah; Alotaibi, Nouf Naif Jahjah; Alharthi, Nawal Ayidh Mayudh (Migration Letters, 2023)
The search for efficient treatment options is necessary since lung cancer is still a major global health concern. In order to better understand how radiation treats lung cancer, this study looked at how dose distribution is affected by lung tissue heterogeneity. Supplies and Procedures: There were two parts to the study’s methodology. First, therapy setups and procedures were establi[1]shed using a computerized treatment planning system. Then, in order to evaluate dosage fluctuations, experimental data were collected using ionization chambers inside a phantom. The study included sophisticated lung cancer treatment planning methods that took dynamic variations in lung density into consideration. To assess dosage estimations, Collapsed Cone Convolution Superposition (CCCS) was used, taking into account variables such relative lung density, treatment geometry, and dose comparisons. Findings: According to analysis, CCCS-based computations showed dosage homogeneity within 1% of adaptive convolution (AC) doses. This suggests that AC is a good substitute because of its faster processing speed. In summary, the research shows that the CCCS algorithm in the treatment planning system can accurately calculate doses, including for heterogeneous media like lung tissue. The accuracy of CCCS in taking tissue density variations into account is confirmed by Monte Carlo calculations.